Adopting The Issue Centred Approach Into Efl Classrooms To Empower The Students’ Decision Making Strategies - Boughani, Siha (جامعة الوادي - University of Eloued, 2022)
Education is a crucial factor that helps in developing critical thinking and enlightening the students to become mature citizens in any community. Preparing students to be reflective and participate in making decisions concerning their society requires the empowerment of their knowledge about social and public issues. The EFL higher education curricula put the learners in front of different social, anthropological, historical and technological problems and questions that raise their awareness about past and present situations. Instead of presenting these subjects in a theoretical approach, Issue Centred Approach (ICA) proposes a different method that aims at not only raising the learners’ awareness but also at helping them be reflective and take the appropriate actions towards these issues and bring change into society. Therefore, this study aims at highlighting how ICA can empower the EFL students’ decision-making strategies for current and future issues. To meet this end, an exploratory questionnaire is administered to 18 EFL teachers at the department of English, University of BEJAIA. The study concludes that the principles of ICA enable the learners, through the interactive, analytical and reflective environment, to discuss and evaluate the alternatives before making any decision).
Teachers’ Perspective
مقال
Keywords: Issues, Issue-Centred Approach, EFL Classroom, Decision Making Strategies